Mini-Craniectomy for Traumatic for Posterior Fossa Acute Liquid Epidural Hematomas in Paediatric Patient: A Case Report - Permana, Padma; Satyarsa, Agung Bagus Sista; Wardhana, Dewa Putu Wisnu (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2025)
Posterior fossa epidural hematoma (PFEDH) is a rare condition, accounting for only 0.1-0.3% of all traumatic brain injuries. Patients can rapidly deteriorate due to brainstem compression caused by bleeding in the posterior cranial fossa. Timely surgical intervention is critical, but currently, there is no consensus on the surgical indication and technical approach for pediatric PFEDH. Case Presentation: A five-year-old boy presented with occipital trauma, headache, vomiting, and altered consciousness after a fall from a 1-meter height. Primary survey was clear with a Glasgow Coma Scale (GCS) score of E3M6V4 and slow pupillary reflexes while secondary examination revealed a 1x2 cm cephalhematoma over the right posterior fossa region. Head CT scan revealed a posterior fossa liquid epidural hematoma measuring 5.4 x 2.2 x 4cm with cerebellar displacement. The patient underwent a mini-craniectomy and recovered with a relatively short operative duration, minimal blood loss, and a short hospital stay without neurological deficits. Mini-craniectomy emerges as a viable and promising alternative procedure in the management of carefully selected pediatric PFEDH cases, particularly those that are liquid or of moderate volume, allowing for efficient evacuation with minimal surgical morbidity with a good prognostic outcome